1998
DOI: 10.1080/14634989808656928
|View full text |Cite
|
Sign up to set email alerts
|

Effect on the planktonic community of the chemical program used to control water hyacinth (Eichhornia crassipes) in Guadalupe Dam, Mexico

Abstract: Guadalupe Dam is a reservoir located into the Metropolitan area of Mexico City, which had been infested with water hyacinth (Eichhornia crassipes) for more than 12 years. In 1993 a management program was conducted in the reservoir. The main activities included the use of aquatic herbicides and mechanical control. The goal of this study was to monitor the composition and fluctuation of the planktonic community during the chemical control program. Five sampling stations were selected. Six samplings were made dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 15 publications
3
17
0
8
Order By: Relevance
“…However, there were no significant thermal differences between the two cyles studied. Similar thermal conditions were found by Lugo et al (1998) in the Guadalupe reservoir. Measurements of pH ( Figure 2B) showed a tendency from neutrality to acidic readings.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…However, there were no significant thermal differences between the two cyles studied. Similar thermal conditions were found by Lugo et al (1998) in the Guadalupe reservoir. Measurements of pH ( Figure 2B) showed a tendency from neutrality to acidic readings.…”
Section: Resultssupporting
confidence: 84%
“…After hyacinth removal values were more variable but no significant differences were found in both periods of sampling (see Figure 3J). Lugo et al (1998) found a slight increase of pH after water hyacinth removal, probably due to algal blooms.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Evidences indicate that natural stressors can modify the sensitivity of the zooplankton community exposed to agrochemicals, so that these organisms are more sensitive to agrochemicals at natural environments than if they are cultivated at controlled conditions in laboratory (LUGO et al, 1998). This could take place because at the natural environment the organisms are exposed to mixtures of chemical compounds, which when combined can cause behavioral, physiological and biochemical changes, death or other adverse effects (HERBRANDSON et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Lugo et al (1998) comprovaram que, na prática, os efeitos deletérios do controle do aguapé no zooplâncton ocorreram em virtude da redução na concentração de oxigênio dissolvido, provocada pela morte da planta, e não diretamente pelos herbicidas diquat e 2,4-D, utilizados na aplicação.…”
Section: Introductionunclassified